Healthcare-seeking behaviour and management of type 2 diabetes: From Ugandan traditional healers’ perspective - Atwine, Fortunate; Hjelm, Katarina (International Journal of Africa Nursing Sciences, 2016)
Background: Healthcare-seeking behaviour has been investigated to a limited extent in persons with diabetes, and the way traditional healers manage diabetes still needs exploration. Aim: To explore healthcare-seeking behaviour and management of type 2 diabetes from the perspective of traditional healers in the folk sector to understand how traditional medicine is integrated into the professional health sector. Design: A qualitative descriptive study. Method: A purposeful sample of 16 traditional healers known in the area. Data were collected by individual semi-structured interviews. Findings: Healthcare was sought from the professional health sector, mainly from the public hospitals, before the patients switched to the traditional healers. Reasons for seeking help from traditional healers were mainly chronic conditions such as diabetes, high blood pressure and the perceived failure of western medicine to manage diabetes. The cost at the healers’ facilities also influenced healthcare seeking because it was perceived to be affordable as it was negotiable and accessible because it was always available. Traditional medicine therapies of patients with diabetes were herbal medicine, nutritional products and counselling, but many patients whose conditions were difficult to manage were told to return to the public hospitals in the professional health sector. Conclusion: Healthcare seeking was inconsistent in character, with a switch between different healthcare providers. Living conditions including treatment costs, healthcare organization, patients’ health beliefs and general condition seemed to influence healthcare seeking practice.
Keywords: Complementary Alternative Medicine; Healthcare-seeking behaviour; Nursing; Traditional healers; Type 2 diabetes; Uganda